KERAGAMAN FENOTIPA IKAN NILA BEST F4,F5 DAN IKAN NILA NIRWANA 2 HASIL SELEKSI DENGAN ANALISIS TRUSS MORFOMETRIK - Irin Iriana Kusmini; Dinar Tri Soelistyowati; Rudhy Gustiano; Peni Pitriani; Vitas Atmadi Prakoso (JURNAL SAINS NATURAL, 2013)
Phenotype Diversity of BEST Nila Fish of F4, F5 and The Nirwana 2 Nila Fish Using Truss Morphometric Analysis          In the framework of the management of genetic resources for long-term development and sustainability of cultivating nila tilapia fish for the evaluation of population genetic resources needs to be done. The purpose of this research was to know the fish of nila tilapia BEST phenotype diversity of F4, F5 and the nila tilapia fish of Nirwana 2 using Truss Morfometrik. The fish from populations of Tilapia BEST fish of F4, F5 and a Nirwana 2 fish each sample taken as many as 20 tails. The measurement was done by specifying points along the body of the fish assay based on morfometrik truss method. The dots were connected one with the others so retrieved 21 characters measuring results. The analys was done using cluster analysis. The observations indicated levels of similarity of truss morfometrik BEST Fish of F4, F5 and the Nirwana 2 fish tilapia very high character except on B6, B3, A3, B1, C1 and D6 that significantly different (p ≤ 0.05).The results gave an indication of the quantity of fish body that  BEST fish was  shorter and rounder than the fish of Nirwana 2 tilapia. Based on the inter population relationship the fish of Nirwana 2 tilapia separated  from BEST nila of F4 and F5.Keywords : BEST tilapia, Nirwana tilapia, truss morfometrik, diversity ABSTRAK         Dalam rangka pengelolaan sumber genetik jangka panjang dan pengembangan budidaya untuk kelestarian ikan nila maka evaluasi sumber daya genetik populasi perlu dilakukan.Tujuan dari penelitian ini adalah mengetahui ragam fenotipe ikan nila BEST F4, F5 dan ikan nila Nirwana 2menggunakanTruss Morfometrik. Ikan nila dari populasi nila BEST F4,F5 dan nila Nirwana2 masing-masing diambil contoh sebanyak 20 ekor. Pengukuran dilakukan dengan menentukan titik-titikacuan sepanjang tubuh ikan uji berdasarkanmetode Truss Morfometrik. Titik-titik dihubungkan satu dengan lainnyasehingga diperoleh 21 karakter hasil pengukuran. Analisis dilakukan dengan menggunakan cluster analysis. Hasil pengamatan menunjukkan tingkat kemiripan truss morfometrik Ikan nila BEST F4, F5 dan ikan nila Nirwana 2 sangat tinggi kecuali pada karakter B6, B3, B1, A3, C1 dan D6 yang berbeda nyata (p≤0,05).Hasil tersebut memberikan indikasi bahwapola badan ikan nila BEST lebih pendek dan bulat dibandingkan ikan nila Nirwana2 yang lebih panjang. Berdasarkan hubungan interpopulasi ikan nila Nirwana 2 terpisah dengan kelompok nila BEST F4 dan F5.Kata kunci : nila BEST, nila Nirwana, truss morfometrik, keragaman